PENGARUH VARIASI WAKTU FERMENTASI TERHADAP KADAR ETANOL HASIL FERMENTASI SINGKONG KUNING (Manihotutillissima Pohl) - Siti Maimunah; Zuhairiah Zuhairiah; Artha Yuliana Sianipar (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Cassava is an agricultural commodity that is widely grown in Indonesia and is an important source of carbohydrates after rice with a content of 34.7%. Yellow cassava is usually served in the form of tape through a fermentation process. This study aims to determine the effect of variations in fermentation time on ethanol content resulting from yellow cassava fermentation. This study used an experimental method with the distillation method using yellow cassava samples which were fermented for 72 hours, 96 hours, and 120 hours. The results of this study indicate that there is an effect of time variation on the ethanol content of fermented yellow cassava with a value of 0.93% (72 hours), 1.00% (96 hours), 1.27% (120 hours) which has a very significant effect (p < 0.01 >). The yield of this fermentation can be determined using the alcohol BJ table.